Action Games and Their Role in the Development of Preschool Children (Intersections of Faith and Culture: American Journal of Religious and Cultural Studies (2993-2599), 2024)
In this article, taking into account the types, features, performance of movement games for the development of the physical qualities of preschool children, simple and complex movements in pairs or singles with creative, plot, sports elements are highlighted.